THE PRACTICE OF VALUES – ISLAMIC VALUES IN PODCAST CONTENT "KEJAR PAKET PINTAR" ON SPOTIFY AND HELP AKHLAKUL KARIMAH CHARACTERS OF ISLAMIC VALUE AGAINST MILLENNIALS - M. Nashoihul Ibad (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2021)
Abstract Podcasts are a form of audio content that is a trend enjoyed by millennials in Indonesia. Content on the internet is increasingly diverse types, audio content is becoming increasingly to be accessed in addition to content in the form of videos such as on Youtube. Listeners' interest in Podcasts one that can be mentioned is the flexibility of its nature, meaning podcast audio can be enjoyed anytime and anywhere, even if sambal does. Work activities or time to rest unwind after work and allow it to be enjoyed as a process to deliver to sleep. This research aims to analyze the values of Islamic da'wah in podcast content that has the potential as a medium for broadcasting Islamic communication. The method used in this research is to use a literature review covering the process of deepening reading and understanding previous studies and analysis of articles. in journals, reference books, research on similar previous research, and Podcast material from Spotify as analysis material.